THE HISTORY OF RESEARCH ON THE POETRY OF HOFIZ KHOREZMI: A BIBLIOMETRIC AND CULTURAL ANALYSIS - Maksudova Nigina Umar kizi (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
The poetry of Hofiz Khorezmi represents one of the most significant contributions to the intellectual and aesthetic traditions of Central Asia. His work, embedded in the Persian-Turkic literary synthesis, has been studied across multiple periods, from early philological catalogues of the 19th century to digital humanities applications of the 21st century. Despite this progress, the historiography of Khorezmi’s scholarship has remained fragmented. This study aims to present a systematic overview of the history of research on Khorezmi’s poetry, with a focus on methodological evolution, bibliometric growth, and the global recognition of his oeuvre.